Highlights of spring migration, 1978 - Shires, Thomas K.et al (1978)
Field report titled "Highlights of Spring Migration" by Thomas K. Shires. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed